Chemical compositions of oil palm trunk at (elaeis guineensis) top and bottom portion / Muhamad Suhaimi Samat - Samat, Muhamad Suhaimi (Faculty of Applied Sciences, 2016)
The growth of oil palm plantation has created the massive amounts of biomass, especially the oil palm trunk. That issue gives negative influence on the environment and replanting operation. The higher amount biomass gives an idea of the possibility to produce a panel product or wood composite product and therefore reduce the dependency of the wood based industry on solid wood. Different portions (top and bottom) and layers (inner and outer) used to determine chemical compositions. The chemical analyses of the OPT in relation to determine moisture content (Me), cold water solubility, hot water solubility, 1% NaOH, ash content, alcohol toluene, lignin, holocellulose, alpha-cellulose were carried out according to the Technical Association of Pulp and Paper Industry standard (TAPPI). The result showed bottoms have high chemical compositions than top portions and outer layer have more chemical composition than inner layer.